Inbreeding, average relatedness coefficient and effective population size in Jaffarabadi buffaloes raised in Brazil - Malhado, Carlos Henrique Mendes; Ferraz, P. C.; Ramos, A. A. [UNESP]; Carneir, P. L.S.; Aragão, E. S.; Barbosa, A. C.B.S.; Carrillo, J. A. (Int Buffalo Information Ctr, 2013)
The major aim of this study was to evaluate the inbreeding (F), average relatedness coefficient (AR) and effective population size (Ne) in the Jaffarabadi buffalo breed from Brazil. Pedigree information of 1,272 animals born from 1966 was used. The effective population size was calculated in two ways: first, computed via individual increase in inbreeding and second estimated by individual increase in coancestry. The known generation numbers were 1.24, 1.76 and 2.64 for complete, equivalent and maximum generation, respectively. The effective size computed via individual increase in coancestry was small with a value of 10.82±1.29. The effective size computed by individual increase in inbreeding (10.40±3.69) was very similar but a little smaller than the previous reported value. The average values of F and AR for the population reference (1,059) were 4.22 and 12.5 percent. The mean of F for inbred animals (319) was 14.0%. The F and AR means were 5.7 and 13.3% for animals with at least 1.5 known equivalent generation and 9.3 and 15.97% for individuals having at least 2.5 equivalent generations known. It was found 78 matings between half sibs (6.14%) and 67 matings (5.27%) between parent-offspring. The estimated inbreeding increase per generation by considering maximum generation, complete generation and equivalent generation were 1.21%, 5.18% and 3.57%, respectively. Considering the uncompleted pedigree, the estimated inbreeding for the reference population could be underestimated.
Keywords: Endogamy; Generation; Pedigree